Students’ motivation on Kampus Mengajar program at English department - Putri, Ayu; Melvina, Melvina; Afriyanti, Rika (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This research aims to determine the motivation of English education students to become teachers after participating in the Kampus Mengajar program. This research is a narrative inquiry research. In this research, researchers conducted interviews with 3 active students at Universitas PGRI Sumatera Barat majoring in English education who had attended Kampus Mengajar. To determine the sampling, the researchers used purposive sampling. The outcome of this research shows that of the 3 students who have participated in the Kampus Mengajar, there is 1 student who has no desire to become a teacher, and does not have a passion as a teacher, but after participating in the Kampus Mengajar program, this student is actually motivated to become a teacher. While the other 2 students already have a passion as teachers and indeed aspire to be teachers, after participating in Kampus Mengajar, they are even more motivated to become teachers. It can be interpreted that motivation is not only present from the internal self, but motivation can also arise due to external encouragement. Keywords: Students’ motivation: Kampus Mengajar program;